The different faces of GATA2 deficiency: implications for therapy and surveillance - Vinci, Luca; Strahm, Brigitte; Speckmann, Carsten; Erlacher, Miriam (Frontiers in Oncology, 2024)
GATA2 deficiency is one of the most common genetic predispositions to pediatric myelodysplastic syndrome (MDS) in children and adolescents. The wide spectrum of disease comprises, among others, hematological, immunological and pulmonary manifestations, as well as occasionally distinct organ anomalies. Due to the elevated risk of progression, nearly all individuals with GATA2-related MDS eventually undergo a hematopoietic stem cell transplantation (HSCT) at some point in their lives. Nevertheless, the optimal timing, method, and even the indication for HSCT in certain cases are still matter of debate and warrant further research.In this article, we report five patients with different hematological and immunological manifestations of GATA2 deficiency ranging from immunodeficiency and refractory cytopenia of childhood without chromosomal aberrations to relapsed MDS-related acute myeloid leukemia. We discuss the adopted strategies, including intensity of surveillance, indication and timing of HSCT, based on morphological, clinical and molecular markers, as well as individual patient needs. We conclude that a better characterization of the natural disease course, a better understanding of the prognostic significance of somatic aberrations and a thorough evaluation of patients´ perspectives and preferences are required to achieve a personalized approach aimed at improving the care of these patients.